Leistungsrelevante Merkmale von Kurz- und Mittelstreckenschwimmern. Eine empirische Erhebung über den Einfluss von anthropometrischen und motorischen Merkmalen auf Zykluslänge, Zyklusfrequenz und ... - Petzner, V. (1992)
The purpose of this study was to determine influences on velocity, stroke rate and distance per stroke in the freestyle swimming event. Therefore 34 finalists (18 sprinters: 10 men, 8 women; 16 middle-distance swimmers: 9 men, 7 women) of the Austrian National Championship were measured and all in all 64 parameters taken. A regression analysis was carried out to find an interaction between these stroke mechanics and anthropometric parameter, strength characteristics - taken on, the isokinetic swimbench - (maximum strength, impulse, explosive strength, work), the elbow angle at the time of maximum bending under water and several others. The regression analysis in the study is differentiating between sprinters and middle distance swimmers and females and males. The results of the whole group of competitors without any differentiation were: Velocity is positively influenced by a large height and long arms, a big exspiratoric chest measurement (measures the form of breast- and backmusculature) long lower legs (advantageous for leg efficiency), a huge strength growth rate and much maximum strength as well as a high training age. A negative effect on velocity has a big body fat proportion and a long duration of the armpull on the isokinetic swimmbench. There is a positive correlation between stroke rate and maximum strength, physique index and age and a negative correlation with specific gravity. The distance per stroke is greater when the forearms are longer, when the strength growth rate is bigger, when the leg impulse is faster and when the duration of the armpull on the swimmbench lasts longer.